Method for efficiently preparing regenerated polyether polyol from waste polyurethane material and polyurethane foam prepared from regenerated polyether polyol

By alcoholylation and extraction separation of waste polyurethane materials, high-functional polyether polyols are prepared and mixed with the original polyether, the problems of difficulty in separation and low functionality in the prior art are solved, and high-efficiency preparation is achieved with excellent Physical properties of recycled polyurethane foam.

CN119431884APending Publication Date: 2025-02-14WANHUA CHEMYANTAI RONGWEI POLYURETHANE CO LTD

Patent Information

Application Number
CN202411796596.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

When recycling waste polyurethane materials in the prior art, there are problems such as difficulty in separation products, low polyether functionality and high viscosity, which affects the physical properties of the preparation of re-foaming and re-grown polyurethane foams.

Method used

Extraction and separation were performed by the spent polyurethane foam reaction solution after alcoholylation, and a high-functional polyether polyol was prepared, and mixed with the original polyether to prepare polyurethane foam.

Benefits of technology

The regenerated polyethers are efficiently separated and regenerated, which improves their functionality and crosslinking density and reduces viscosity. The prepared regenerated polyurethane foam has the advantages of low thermal conductivity, high compression strength, and good mold release performance, supporting the efficient recycling of polyurethane. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005176890680000161
    Figure BDA0005176890680000161
  • Figure BDA0005176890680000162
    Figure BDA0005176890680000162
  • Figure BDA0005176890680000171
    Figure BDA0005176890680000171
Patent Text Reader

Abstract

The invention provides a method for efficiently preparing regenerated polyether polyol by using a waste polyurethane material and polyurethane foam prepared from the waste polyurethane material, the method comprises the following steps: 1) crushing waste polyurethane foam, adding an alcoholysis agent and a catalyst, and carrying out a closed reaction in an inert gas atmosphere to obtain a mixed product; and 2) firstly adding a neutralizer into the mixed product to remove amines and urea, then adding an organic extractant, and extracting and separating to obtain the regenerated polyether polyol. The polyether polyol prepared by the method disclosed by the invention can be further used for synthesizing a rigid foam polyurethane material, demolding can be obviously improved, and the space for recycling waste foam is expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyurethane recovery, and in particular to a method for efficiently preparing regenerated polyether polyols by utilizing waste polyurethane materials and polyurethane foam prepared thereby. Background Art

[0002] As a structural material and thermal insulation material with good performance, rigid polyurethane foam is widely used in the thermal insulation layer of refrigerators, freezers, cold storage, refrigerated trucks, and other boxes, as well as in the thermal insulation layer of buildings, storage tanks, and pipelines. In the process of industrial development, the actual demand for polyurethane has increased year by year, and a large amount of waste rigid foam has also appeared. The recycling and reuse of waste polyurethane is imminent. The traditional landfill incineration method not only occupies land and consumes energy, but also easily produces harmful substances that harm water and soil resources; the physical recycling method has high requirements for foam classification and limited processing capacity.

[0003] Since the polymerization reaction of polyurethane is reversible, chemical degradation of polyurethane is highly feasible, mainly in the following ways: alcoholysis, ammonolysis, acidolysis and hydrolysis. Among them, ammonolysis, acidolysis and hydrolysis often need to react under high temperature and high pressure environment, with high equipment requirements, high operating risks and high separation difficulty, which greatly limits the development of industrialization. The alcoholysis method uses small molecular alcohols such as methanol, ethanol and propanol as alcoholysis agents to obtain high-functional polyether polyols through ester exchange reactions. Its advantages are mild reaction conditions and easy access to raw materials, but there are still problems such as difficulty in separating products, low polyether functionality and high viscosity, which affect the physical properties of the regenerated polyether preparation and re-foaming and the regenerated polyurethane foam.

[0004] At present, in the field of polyurethane foam recycling, the large molecular weight and high viscosity of polyurethane make it difficult to separate from the product after the reaction, resulting in low average functionality and high viscosity of the product system. CN115677975A mentions the use of external emulsification method to synthesize water-based polyurethane without hydrophilic group, to achieve efficient separation of reactants and products, and finally obtain a higher yield. CN117580913A mentions that it is difficult to activate the CN bond during the reaction, and the use of potassium salt catalyst for alcoholysis has a fast reaction rate, a large degree of selective cleavage, and excellent mechanical properties of the regenerated polyether foaming.

[0005] In summary, the existing technology uses alcoholysis to recycle waste polyurethane, but there are still problems such as difficulty in separating products, low polyether functionality, and high viscosity, which affect the physical properties of the regenerated polyether for preparing re-foaming and the regenerated polyurethane foam. Summary of the invention

[0006] In view of the above-mentioned shortcomings in the prior art, the present invention provides a method for efficiently preparing regenerated polyether polyols by using waste polyurethane materials, that is, the waste polyurethane foam reaction liquid after alcoholysis is efficiently separated by extraction to prepare high-functionality polyether polyols. The polyurethane foam prepared by mixing the regenerated polyether prepared by the above method with the original polyether has low thermal conductivity (18-20.5mW / (m·k)), high compressive strength (density 26-33kg / m 3 , 140 ~ 180kPa), good demoulding (4min demoulding expansion 1.7 ~ 3.8mm) and other characteristics are expected to achieve efficient recycling of polyurethane.

[0007] Another object of the present invention is to provide a polyurethane foam material prepared by using the above-mentioned recycled polyether polyol.

[0008] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solution:

[0009] A method for efficiently preparing recycled polyether polyols using waste polyurethane materials comprises the following steps:

[0010] S1. Grind the waste rigid polyurethane foam material, add alcoholysis agent and catalyst in proportion, carry out alcoholysis reaction under an inert gas atmosphere, and centrifuge after the reaction is completed;

[0011] S2. Take the upper liquid phase after centrifugation, add a neutralizing agent to adjust the pH, then transfer it to a three-necked flask and continue heating for neutralization reaction. After the reaction is completed, the alcoholysis product is centrifuged and separated. After cooling, an organic extractant is added to extract and separate the liquid. The upper inorganic phase is dehydrated by a dehydrating agent to obtain a regenerated polyether polyol (RPOL).

[0012] In the present invention, in S1, the waste rigid polyurethane foam material is crushed into particles with a diameter less than 30 mm, preferably less than 10 mm.

[0013] In the present invention, a hydroxy alcohol with a single reaction site and low molecular weight is selected, preferably one or two of methanol, ethanol, 1-propanol, 1-butanol and 2-butanol, and more preferably 2-butanol. The mass ratio of the alcoholysis agent to the polyurethane material is 1:1 to 1:4, such as 1:1, 1:2, 1:3 or 1:4, preferably 1:2.

[0014] In the present invention, the catalyst is an organic metal compound, preferably an organic metal compound with suitable basicity, such as titanium butoxide, titanium glycolate, potassium octoate, stannous octoate, potassium acetate, etc., preferably potassium acetate. The amount of the catalyst added is 0.3-1.5% of the total mass of the polyurethane material and the alcoholysis agent, such as 0.5%, 0.6%, 0.9%, 1.0%, 1.3%, 1.4%, etc., preferably 0.8-1.2%, more preferably 1.2%.

[0015] In the present invention, the reaction temperature of the alcoholysis reaction in S1 is 130-170°C, such as 140°C, 150°C, 160°C, etc., and the reaction time is 3-6h, such as 4h, 5h, etc.

[0016] In the present invention, the neutralizer in S2 is selected from any one of hydrochloric acid, oxalic acid, nitric acid, phosphoric acid, and dilute sulfuric acid, preferably hydrochloric acid; the concentration of the neutralizer is 0.5-2 mol / L, preferably 1 mol / L, and the neutralizer is added to adjust the pH to 5-7, for example, 6; the reaction temperature of the neutralization reaction is 35-50°C, for example, 40°C, 45°C, etc., and the reaction time is 2-4h, for example, 3h.

[0017] In the present invention, the dehydrating agent described in S2 generally includes calcium chloride, anhydrous copper sulfate, magnesium chloride and sodium carbonate, preferably calcium chloride, wherein the amount of the dehydrating agent added is 8-20% of the mass of the alcoholysis product, for example, 10%, 12%, 15%, 18% of the mass of the alcoholysis product, etc.

[0018] In the present invention, the extractant S2 generally includes ethyl acetate, carbon tetrachloride, gasoline, butanone and cyclohexane, preferably cyclohexane, wherein the amount of the extractant added is 10-20% of the mass of the alcoholysis product, for example, 10%, 12%, 15%, 18% of the mass of the alcoholysis product, etc.

[0019] The object of the present invention is to provide a high-functionality polyether polyol.

[0020] In the present invention, the average functionality of the prepared regenerated polyether polyol is 2 to 6, preferably 3 to 5, the hydroxyl value is 200 to 1000 mg KOH / g, preferably 300 to 400 mg KOH / g, the viscosity at room temperature 25°C is 2000 to 12000 cp, preferably 3000 to 6000 cp, and the acid value is 0.1 to 1.5 mg KOH / g, preferably 0.2 to 0.5 mg KOH / g.

[0021] In the present invention, the waste polyurethane used as the degradable raw material can be waste refrigerators, freezers, etc., which have a low market price, a wide range of acquisition channels, mild degradation conditions, low requirements on equipment, and strong operability.

[0022] On the other hand, a polyurethane foam is provided which is prepared by obtaining polyether polyol by alcoholysis of waste polyurethane materials. The polyether polyol of the polyurethane foam is prepared by the above method, and replaces 10% to 100%, preferably 40 to 60%, and more preferably 50% of the original polyether, and is used to prepare the regenerated polyurethane foam. The overall core density of the polyurethane foam is 26 to 33 kg / m 3, compression strength 140 ~ 180kPa, 4min demolding expansion 1.7 ~ 3.8mm, thermal conductivity 18 ~ 20.5mW / (m · k), water absorption 0.6 ~ 1%, closed porosity 97 ~ 99%.

[0023] In a preferred embodiment, the preparation method of the regenerated polyurethane foam is as follows: the regenerated polyether replaces half of the original polyether, and then the catalyst, water, and silicone oil are weighed according to the original formula, and after stirring and mixing, the cyclopentane catalyst is added, mixed with Wanhua PM-200 in a fixed ratio, and quickly poured into an open vertical mold, the lid is fastened, and the mold is demolded after 8 minutes to obtain the regenerated polyurethane foam, and its thermal conductivity, core density, and compression strength are measured. The same ratio is placed in an open horizontal mold, the lid is fastened, and the mold is demolded after 4 minutes, and its demolding expansion can be measured.

[0024] Compared with the prior art, the present invention has the following positive effects:

[0025] The alcoholysis scheme provided by the present invention uses a monofunctional, low-molecular-weight hydroxy alcohol as an alcoholysis agent, and the polarity difference between the obtained ester exchange product and the regenerated polyether is large; an organic extractant with moderate polarity is used, starting from the intrinsic structure of the molecule, and utilizing the polarity difference between the product ends, i.e., the hydroxyl group and the alkyl group, to achieve efficient physical separation, with high separation efficiency and low energy consumption.

[0026] The recycled polyether prepared by the method of the present invention has high functionality, high cross-linking density and low viscosity; the recycled polyurethane prepared by foaming after mixing with the original polyether has the advantages of low thermal conductivity, good demoulding performance, high compression strength under low density conditions, etc., and is expected to realize large-scale recycling and reuse of waste foam. DETAILED DESCRIPTION

[0027] The technical solution of the present invention is further illustrated by specific embodiments below, but the protection scope of the present invention is not limited thereto. Within the technical scope disclosed in the present invention, changes or replacements of the same or similar technical features should be covered within the protection scope of the present invention.

[0028] The main raw materials involved in the following examples are as follows:

[0029] Rigid polyurethane foam: Hisense discarded refrigerator foam, waste pipe insulation foam, waste refrigerated truck body foam;

[0030] The alcoholysis agent and dehydrating agent used in the present invention are purchased from Shanghai Titan Technology Co., Ltd., with AR grade purity, purity ≥ 99%;

[0031] Titanium butoxide, titanium glycolate, potassium octoate, stannous octoate, potassium acetate, MacLean, AR;

[0032] Ethyl acetate, carbon tetrachloride, gasoline, butanone, and cyclohexane, MacLean, AR;

[0033] Sorbitol polyether polyol, glycerol polyether polyol, PM200, Wanhua Chemical Co., Ltd.;

[0034] Cyclopentane, composite catalyst, Sinochem Blue Sky;

[0035] Silicone oil surfactant, Nanjing Meside Co., Ltd.

[0036] The main test instruments involved in the following embodiments are as follows:

[0037] Compression testing machine: Shanghai Xieqiang Instrument Manufacturing Co., Ltd., CTM200 series material testing machine;

[0038] Thermal conductivity tester: Nanjing Huicheng Instrument Co., Ltd., HCDR-S Shuntai plane source method thermal conductivity meter;

[0039] Automatic potentiometric titrator: Swiss Metrohm 905 Titrando automatic potentiometric titrator.

[0040] The main characterization methods involved in the following examples are as follows:

[0041] The viscosity, hydroxyl value, acid value, molecular weight, average functionality of recycled polyether, as well as the density, compression strength, thermal conductivity and other results of recycled polyurethane foam are all measured according to national standards:

[0042] Recycled polyether viscosity test standard: GB / T12008.7-2010;

[0043] Recycled polyether hydroxyl value test standard: GB / T12008.3-2009;

[0044] Recycled polyether acid value test standard: GB-T 12008.5-2010;

[0045] The molecular weight of the regenerated polyether was tested by gel permeation chromatography;

[0046] Average functionality of recycled polyether

[0047] Foam core density test according to standard: GB / T 6343-2009;

[0048] Foam thermal conductivity test is in accordance with the standard: GB / T 10295-2008;

[0049] Foam compression strength test according to standard: GB / T 8813-2008;

[0050] Foam demoulding expansion test: foam in a horizontal mold, measure the expansion of 6 points in the center after 4 minutes of reaction and calculate the average value.

[0051] Example 1

[0052] The insulation foam disassembled from Hisense waste refrigerators was crushed into particles with an average size of 10 mm. After screening, 100 g of waste foam, 50 g of methanol, and 1.8 g of titanium butoxide were put into a 500 mL round-bottom flask. After the temperature rose to 140 ° C, the reaction was carried out for 4 hours. After the reaction was completed, the product was placed in a centrifuge and centrifuged at a speed of 5000 rpm to obtain a wine-red alcoholysis product. 50 g of the alcoholysis crude product was neutralized with 1 mol / L dilute sulfuric acid to adjust the pH to 6. After the temperature rose to 40 ° C, the reaction was carried out for 4 hours, and then placed in a separating funnel. After cooling, it was extracted with ethyl acetate. After separation, anhydrous copper sulfate was added to the upper liquid to remove water. After filtering, a brown-yellow regenerated polyether polyol was obtained. The entire reaction was carried out under nitrogen protection. The specific characterization results of the regenerated polyol are shown in Table 1.

[0053] At room temperature, 50 g of recycled polyether, 10 g of sorbitol polyether polyol, 36.4 g of glycerol polyether polyol, 0.2 g of triethylenediamine, 1.4 g of NN, dimethyl-cyclohexylamine, 2 g of deionized water and 16 g of cyclopentane were weighed and mixed for 1 h, then mixed with 125 g of Wanhua PM-200, stirred for 5 seconds and quickly poured into a vertical mold (size: 300 mm long, 50 mm wide, 700 mm high). Quickly pour it into an open vertical mold, fasten the lid, and demold after 8 minutes to obtain a light yellow recycled polyurethane foam. The characterization results of the polyurethane foam are shown in Table 2. Similarly, 50 g of recycled polyether, 10 g of sorbitol polyether polyol, 36.4 g of glycerol polyether polyol, 0.2 g of triethylenediamine, 1.4 g of NN, dimethyl-cyclohexylamine, 2 g of deionized water and 16 g of cyclopentane were weighed at room temperature, shaken and mixed for 1 hour, and then mixed with 125 g of Wanhua PM-200. After stirring for 5 seconds, the mixture was quickly poured into a horizontal mold (size: 500 mm long, 500 mm wide, and 100 mm high). The mixture was quickly poured into an open horizontal mold, the lid was fastened, and the mold was demolded after 4 minutes. The foam was quickly taken out, and the average expansion value of the 6 points in the center was selected. The characterization results of the polyurethane foam are shown in Table 2.

[0054] Example 2

[0055] The insulation foam disassembled from Hisense waste refrigerators was crushed into particles with an average size of 10 mm. After screening, 200 g of waste foam, 100 g of ethanol, and 3.6 g of ethylene glycol titanium were put into a 500 mL round-bottom flask. After the temperature rose to 140 ° C, the reaction was carried out for 4 hours. After the reaction was completed, the product was placed in a centrifuge and centrifuged at a speed of 5000 rpm to obtain a wine-red alcoholysis product. 100 g of alcoholysis crude product was neutralized with 1 mol / L oxalic acid to adjust pH = 6. After the temperature rose to 40 ° C, the reaction was carried out for 4 hours, and then placed in a separating funnel. After cooling, it was extracted with gasoline. After separation, magnesium chloride was added to the upper liquid to remove water, and brown regenerated polyether polyols were obtained. The entire reaction was carried out under nitrogen protection. The specific characterization results of the regenerated polyols are shown in Table 1.

[0056] 30 g of recycled polyether, 30 g of sorbitol polyether polyol, 36.4 g of glycerol polyether polyol, 1.4 g of NN, dimethyl-cyclohexylamine, 2 g of deionized water and 16 g of cyclopentane were weighed at room temperature, and after shaking and mixing for 1 h, they were mixed with 125 g of Wanhua PM-200, stirred for 5 seconds, and then quickly poured into a vertical mold (size: 300 mm long, 50 mm wide, and 700 mm high). Quickly pour it into an open vertical mold, fasten the lid, and demold after 8 minutes to obtain a light yellow recycled polyurethane foam. The characterization results of the polyurethane foam are shown in Table 2. Similarly, 30 g of recycled polyether, 30 g of sorbitol polyether polyol, 36.4 g of glycerol polyether polyol, 0.2 g of triethylenediamine, 1.4 g of NN, dimethyl-cyclohexylamine, 2 g of deionized water and 16 g of cyclopentane were weighed at room temperature, and after shaking and mixing for 1 hour, they were mixed with 125 g of Wanhua PM-200, stirred for 5 seconds, and then quickly poured into a horizontal mold (size: 500 mm long, 500 mm wide, 100 mm high). Quickly pour it into an open horizontal mold, fasten the lid, demold after 4 minutes, quickly take out the foam, select 6 points in the center to measure the average expansion value, and the characterization results of the polyurethane foam are shown in Table 2.

[0057] Example 3

[0058] The insulation foam disassembled from Hisense waste refrigerators was crushed into particles with an average size of 10 mm. After screening, 150 g of waste foam, 75 g of 1-propanol, and 2.7 g of potassium octanoate were put into a 500 mL round-bottom flask. After the temperature rose to 140 ° C, the reaction was carried out for 4 hours. After the reaction was completed, the product was placed in a centrifuge and centrifuged at a speed of 5000 rpm to obtain a wine-red alcoholysis product. 80 g of the alcoholysis crude product was neutralized with 1 mol / L nitric acid to adjust the pH to 6. After the temperature rose to 40 ° C and the reaction was carried out for 4 hours, it was placed in a separating funnel, cooled, extracted and filtered with butanone, and sodium carbonate was added to the upper liquid after separation to remove water, and a yellow-brown regenerated polyether polyol was obtained. The entire reaction was carried out under nitrogen protection. The specific characterization results of the regenerated polyol are shown in Table 1.

[0059] At room temperature, 50 g of recycled polyether, 10 g of sorbitol polyether polyol, 36.4 g of glycerol polyether polyol, 0.2 g of triethylenediamine, 1.4 g of NN, dimethyl-cyclohexylamine, 2 g of deionized water and 16 g of cyclopentane were weighed and mixed for 1 h, then mixed with 125 g of Wanhua PM-200, stirred for 5 seconds and quickly poured into a vertical mold (size: 300 mm long, 50 mm wide, 700 mm high). Quickly pour it into an open vertical mold, fasten the lid, and demold after 8 minutes to obtain a light yellow recycled polyurethane foam. The characterization results of the polyurethane foam are shown in Table 2. Similarly, 50 g of recycled polyether, 10 g of sorbitol polyether polyol, 36.4 g of glycerol polyether polyol, 0.2 g of triethylenediamine, 1.4 g of NN, dimethyl-cyclohexylamine, 2 g of deionized water and 16 g of cyclopentane were weighed at room temperature, and after shaking and mixing for 1 hour, they were mixed with 125 g of Wanhua PM-200, stirred for 5 seconds, and then quickly poured into a horizontal mold (size: 500 mm long, 500 mm wide, 100 mm high). Quickly pour it into an open horizontal mold, fasten the lid, demold after 4 minutes, quickly take out the foam, select 6 points in the center to measure the average expansion value, and the characterization results of the polyurethane foam are shown in Table 2.

[0060] Example 4

[0061] The insulation foam disassembled from Hisense's waste refrigerator was crushed into particles with an average size of 10 mm. After screening, 100 g of waste foam, 50 g of 1-butanol, and 1.8 g of stannous octoate were put into a 500 mL round-bottom flask. After the temperature rose to 140 ° C, the reaction was carried out for 4 hours. After the reaction was completed, the product was placed in a centrifuge and centrifuged at a speed of 5000 rpm to obtain a wine-red alcoholysis product. 50 g of the alcoholysis crude product was neutralized with 1 mol / L phosphoric acid to adjust the pH to 6. After the temperature rose to 40 ° C and the reaction was carried out for 4 hours, it was placed in a separating funnel, cooled and extracted and filtered with carbon tetrachloride. After separation, calcium chloride was added to the upper liquid to remove water, and a yellow-brown regenerated polyether polyol was obtained. The entire reaction was carried out under nitrogen protection. The specific characterization results of the regenerated polyol are shown in Table 1.

[0062] At room temperature, 50 g of recycled polyether, 10 g of sorbitol polyether polyol, 36.4 g of glycerol polyether polyol, 0.2 g of triethylenediamine, 1.4 g of NN, dimethyl-cyclohexylamine, 2 g of deionized water and 16 g of cyclopentane were weighed and mixed for 1 h, then mixed with 125 g of Wanhua PM-200, stirred for 5 seconds and quickly poured into a vertical mold (size: 300 mm long, 50 mm wide, 700 mm high). Quickly pour it into an open vertical mold, fasten the lid, and demold after 8 minutes to obtain a light yellow recycled polyurethane foam. The characterization results of the polyurethane foam are shown in Table 2. Similarly, 50 g of recycled polyether, 10 g of sorbitol polyether polyol, 36.4 g of glycerol polyether polyol, 0.2 g of triethylenediamine, 1.4 g of NN, dimethyl-cyclohexylamine, 2 g of deionized water and 16 g of cyclopentane were weighed at room temperature, and after shaking and mixing for 1 hour, they were mixed with 125 g of Wanhua PM-200, stirred for 5 seconds, and then quickly poured into a horizontal mold (size: 500 mm long, 500 mm wide, 100 mm high). Quickly pour it into an open horizontal mold, fasten the lid, demold after 4 minutes, quickly take out the foam, select 6 points in the center to measure the average expansion value, and the characterization results of the polyurethane foam are shown in Table 2.

[0063] Example 5

[0064] The insulation foam disassembled from Hisense waste refrigerators was crushed into particles with an average size of 10 mm. After screening, 200 g of waste foam, 100 g of 2-butanol, and 1.8 g of potassium acetate were put into a 500 mL round-bottom flask. After the temperature rose to 180 ° C, the reaction was carried out for 4 hours. After the reaction was completed, the product was placed in a centrifuge and centrifuged at a speed of 5000 rpm to obtain a wine-red alcoholysis product. 50 g of the alcoholysis crude product was neutralized with 1 mol / L hydrochloric acid to adjust the pH to 6. After the temperature rose to 40 ° C and the reaction was carried out for 4 hours, it was placed in a separating funnel, cooled, extracted and filtered with cyclohexane, and calcium chloride was added to the upper liquid after separation to remove water, and a yellow-brown regenerated polyether polyol was obtained. The entire reaction was carried out under nitrogen protection. The specific characterization results of the regenerated polyol are shown in Table 1.

[0065] 70 g of recycled polyether, 10 g of sorbitol polyether polyol, 16.4 g of glycerol polyether polyol, 0.2 g of triethylenediamine, 1.4 g of NN, dimethyl-cyclohexylamine, 2 g of deionized water and 16 g of cyclopentane were weighed at room temperature, and after shaking and mixing for 1 hour, they were mixed with 125 g of Wanhua PM-200, stirred for 5 seconds, and then quickly poured into a vertical mold (size: 300 mm long, 50 mm wide, and 700 mm high). Quickly pour it into an open vertical mold, fasten the lid, and demold after 8 minutes to obtain a light yellow recycled polyurethane foam. The characterization results of the polyurethane foam are shown in Table 2. Similarly, 70 g of recycled polyether, 10 g of sorbitol polyether polyol, 16.4 g of glycerol polyether polyol, 0.2 g of triethylenediamine, 1.4 g of NN, dimethyl-cyclohexylamine, 2 g of deionized water and 16 g of cyclopentane were weighed at room temperature, and after shaking and mixing for 1 hour, they were mixed with 125 g of Wanhua PM-200, stirred for 5 seconds, and then quickly poured into a horizontal mold (size: 500 mm long, 500 mm wide, 100 mm high). Quickly pour it into an open horizontal mold, fasten the lid, demold after 4 minutes, quickly take out the foam, select 6 points in the center to measure the average expansion value, and the characterization results of the polyurethane foam are shown in Table 2.

[0066] Comparative Example 1

[0067] Compared with Example 1, the difference is that no extraction separation is adopted.

[0068] The insulation foam disassembled from Hisense waste refrigerators was crushed into particles with an average size of 10 mm. After screening, 100 g of waste foam, 50 g of methanol, and 1.8 g of titanium butoxide were put into a 500 mL round-bottom flask. After the temperature rose to 140 ° C, the reaction was carried out for 4 hours. After the reaction was completed, the product was placed in a centrifuge and centrifuged at a speed of 5000 rpm to obtain a wine-red alcoholysis product. 50 g of the alcoholysis crude product was neutralized with 1 mol / L dilute sulfuric acid to adjust the pH to 6. After the temperature rose to 40 ° C and the reaction was carried out for 4 hours, anhydrous copper sulfate was directly added to remove water after cooling. After filtering, a brown-yellow regenerated polyether polyol was obtained. The entire reaction was carried out under nitrogen protection. The specific characterization results of the regenerated polyol are shown in Table 1.

[0069] At room temperature, 50 g of recycled polyether, 10 g of sorbitol polyether polyol, 36.4 g of glycerol polyether polyol, 0.2 g of triethylenediamine, 1.4 g of NN, dimethyl-cyclohexylamine, 2 g of deionized water and 16 g of cyclopentane were weighed and mixed for 1 h, then mixed with 125 g of Wanhua PM-200, stirred for 5 seconds and quickly poured into a vertical mold (size: 300 mm long, 50 mm wide, 700 mm high). Quickly pour it into an open vertical mold, fasten the lid, and demold after 8 minutes to obtain a light yellow recycled polyurethane foam. The characterization results of the polyurethane foam are shown in Table 2. At room temperature, 50 g of recycled polyether, 10 g of sorbitol polyether polyol, 36.4 g of glycerol polyether polyol, 0.2 g of triethylenediamine, 1.4 g of NN, dimethyl-cyclohexylamine, 2 g of deionized water and 16 g of cyclopentane were weighed and mixed for 1 h, then mixed with 125 g of Wanhua PM-200, stirred for 5 seconds and quickly poured into a horizontal mold (size: 500 mm long, 500 mm wide, 100 mm high). The mold was quickly poured into an open horizontal mold, the lid was fastened, and the mold was demolded after 4 minutes. The foam was quickly taken out, and the average expansion value of the 6 points in the center was selected. The characterization results of the polyurethane foam are shown in Table 2.

[0070] Comparative Example 2

[0071] Compared with Example 1, the difference is that the alcoholysis agent uses polyhydroxy ethylene glycol.

[0072] The insulation foam disassembled from Hisense waste refrigerators was crushed into particles with an average size of 10 mm. After screening, 200 g of waste foam, 100 g of ethylene glycol, and 3.6 g of ethylene glycol titanium were put into a 500 mL round-bottom flask. After the temperature rose to 140 ° C, the reaction was carried out for 4 hours. After the reaction was completed, the product was placed in a centrifuge and centrifuged at a speed of 5000 rpm to obtain a wine-red alcoholysis product. 100 g of the alcoholysis crude product was neutralized with 1 mol / L oxalic acid to adjust the pH to 6. After the temperature rose to 40 ° C and the reaction was carried out for 4 hours, it was placed in a separating funnel, cooled and extracted with gasoline, and magnesium chloride was added to the upper liquid after separation to remove water, and a brown regenerated polyether polyol was obtained. The entire reaction was carried out under nitrogen protection. The specific characterization results of the regenerated polyol are shown in Table 1.

[0073] At room temperature, 50 g of recycled polyether, 10 g of sorbitol polyether polyol, 36.4 g of glycerol polyether polyol, 0.2 g of triethylenediamine, 1.4 g of NN, dimethyl-cyclohexylamine, 2 g of deionized water and 16 g of cyclopentane were weighed and mixed for 1 h, then mixed with 125 g of Wanhua PM-200, stirred for 5 seconds and quickly poured into a vertical mold (size: 300 mm long, 50 mm wide, 700 mm high). Quickly pour it into an open vertical mold, fasten the lid, and demold after 8 minutes to obtain a light yellow recycled polyurethane foam. The characterization results of the polyurethane foam are shown in Table 2. Similarly, 50 g of recycled polyether, 10 g of sorbitol polyether polyol, 36.4 g of glycerol polyether polyol, 0.2 g of triethylenediamine, 1.4 g of NN, dimethyl-cyclohexylamine, 2 g of deionized water and 16 g of cyclopentane were weighed at room temperature, shaken and mixed for 1 hour, and then mixed with 125 g of Wanhua PM-200. After stirring for 5 seconds, the mixture was quickly poured into a horizontal mold (size: 500 mm long, 500 mm wide, and 100 mm high). The mixture was quickly poured into an open horizontal mold, the lid was fastened, and the mold was demolded after 4 minutes. The foam was quickly taken out, and the average expansion value of the 6 points in the center was selected. The characterization results of the polyurethane foam are shown in Table 2.

[0074] Comparative Example 3

[0075] Compared with Example 1, the difference is that no neutralizing agent is used to adjust the pH.

[0076] The insulation foam disassembled from Hisense waste refrigerators was crushed into particles with an average size of 10 mm. After screening, 150 g of waste foam, 75 g of 1-propanol, and 2.7 g of potassium octanoate were put into a 500 mL round-bottom flask. After the temperature rose to 140 ° C, the reaction was carried out for 4 hours. After the reaction was completed, the product was placed in a centrifuge and centrifuged at a speed of 5000 rpm to obtain a wine-red alcoholysis product. 80 g of the alcoholysis crude product was placed in a separatory funnel and directly extracted and filtered with butanone. After separation, sodium carbonate was added to the upper liquid to remove water, and a yellow-brown regenerated polyether polyol was obtained. The entire reaction was carried out under nitrogen protection. The specific characterization results of the regenerated polyol are shown in Table 1.

[0077] At room temperature, 50 g of recycled polyether, 10 g of sorbitol polyether polyol, 36.4 g of glycerol polyether polyol, 0.2 g of triethylenediamine, 1.4 g of NN, dimethyl-cyclohexylamine, 2 g of deionized water and 16 g of cyclopentane were weighed and mixed for 1 h, then mixed with 125 g of Wanhua PM-200, stirred for 5 seconds and quickly poured into a vertical mold (size: 300 mm long, 50 mm wide, 700 mm high). Quickly pour it into an open vertical mold, fasten the lid, and demold after 8 minutes to obtain a light yellow recycled polyurethane foam. The characterization results of the polyurethane foam are shown in Table 2. Similarly, 50 g of recycled polyether, 10 g of sorbitol polyether polyol, 36.4 g of glycerol polyether polyol, 0.2 g of triethylenediamine, 1.4 g of NN, dimethyl-cyclohexylamine, 2 g of deionized water and 16 g of cyclopentane were weighed at room temperature, shaken and mixed for 1 hour, and then mixed with 125 g of Wanhua PM-200. After stirring for 5 seconds, the mixture was quickly poured into a horizontal mold (size: 500 mm long, 500 mm wide, and 100 mm high). The mixture was quickly poured into an open horizontal mold, the lid was fastened, and the mold was demolded after 4 minutes. The foam was quickly taken out, and the average expansion value of the 6 points in the center was selected. The characterization results of the polyurethane foam are shown in Table 2.

[0078] Comparative Example 4

[0079] Compared with Example 1, the difference is that the extractant is petroleum ether.

[0080] The insulation foam disassembled from Hisense's waste refrigerator was crushed into particles with an average size of 10 mm. After screening, 100 g of waste foam, 50 g of 1-butanol, and 1.8 g of stannous octoate were put into a 500 mL round-bottom flask. After the temperature rose to 140 ° C, the reaction was carried out for 4 hours. After the reaction was completed, the product was placed in a centrifuge and centrifuged at a speed of 5000 rpm to obtain a wine-red alcoholysis product. 50 g of the alcoholysis crude product was neutralized with 1 mol / L phosphoric acid to adjust the pH to 6. After the temperature rose to 40 ° C and the reaction was carried out for 4 hours, it was placed in a separating funnel, cooled, extracted and filtered with petroleum ether, and calcium chloride was added to the upper liquid after separation to remove water, and a yellow-brown regenerated polyether polyol was obtained. The entire reaction was carried out under nitrogen protection. The specific characterization results of the regenerated polyol are shown in Table 1.

[0081] At room temperature, 50 g of recycled polyether, 10 g of sorbitol polyether polyol, 36.4 g of glycerol polyether polyol, 0.2 g of triethylenediamine, 1.4 g of NN, dimethyl-cyclohexylamine, 2 g of deionized water and 16 g of cyclopentane were weighed and mixed for 1 h, then mixed with 125 g of Wanhua PM-200, stirred for 5 seconds and quickly poured into a vertical mold (size: 300 mm long, 50 mm wide, 700 mm high). Quickly pour it into an open vertical mold, fasten the lid, and demold after 8 minutes to obtain a light yellow recycled polyurethane foam. The characterization results of the polyurethane foam are shown in Table 2. Similarly, 50 g of recycled polyether, 10 g of sorbitol polyether polyol, 36.4 g of glycerol polyether polyol, 0.2 g of triethylenediamine, 1.4 g of NN, dimethyl-cyclohexylamine, 2 g of deionized water and 16 g of cyclopentane were weighed at room temperature, shaken and mixed for 1 hour, and then mixed with 125 g of Wanhua PM-200. After stirring for 5 seconds, the mixture was quickly poured into a horizontal mold (size: 500 mm long, 500 mm wide, and 100 mm high). The mixture was quickly poured into an open horizontal mold, the lid was fastened, and the mold was demolded after 4 minutes. The foam was quickly taken out, and the average expansion value of the 6 points in the center was selected. The characterization results of the polyurethane foam are shown in Table 2.

[0082] Comparative Example 5

[0083] Compared with Example 1, the difference is that the pH of the neutralization solution is adjusted to 8, and benzene is used as the extractant.

[0084] The insulation foam disassembled from Hisense waste refrigerators was crushed into particles with an average size of 10 mm. After screening, 200 g of waste foam, 100 g of 2-butanol, and 1.8 g of potassium acetate were put into a 500 mL round-bottom flask. After the temperature rose to 180 ° C, the reaction was carried out for 4 hours. After the reaction was completed, the product was placed in a centrifuge and centrifuged at a speed of 5000 rpm to obtain a wine-red alcoholysis product. 50 g of the alcoholysis crude product was neutralized with 1 mol / L hydrochloric acid to adjust the pH to 8. After the temperature rose to 40 ° C, the reaction was carried out for 4 hours, and then placed in a separating funnel. After cooling, it was extracted and filtered with benzene. After separation, calcium chloride was added to the upper liquid to remove water, and a yellow-brown regenerated polyether polyol was obtained. The entire reaction was carried out under nitrogen protection. The specific characterization results of the regenerated polyol are shown in Table 1.

[0085] At room temperature, 50 g of recycled polyether, 10 g of sorbitol polyether polyol, 36.4 g of glycerol polyether polyol, 0.2 g of triethylenediamine, 1.4 g of NN, dimethyl-cyclohexylamine, 2 g of deionized water and 16 g of cyclopentane were weighed and mixed for 1 h, then mixed with 125 g of Wanhua PM-200, stirred for 5 seconds and quickly poured into a vertical mold (size: 300 mm long, 50 mm wide, 700 mm high). Quickly pour it into an open vertical mold, fasten the lid, and demold after 8 minutes to obtain a light yellow recycled polyurethane foam. The characterization results of the polyurethane foam are shown in Table 2. Similarly, 50 g of recycled polyether, 10 g of sorbitol polyether polyol, 36.4 g of glycerol polyether polyol, 0.2 g of triethylenediamine, 1.4 g of NN, dimethyl-cyclohexylamine, 2 g of deionized water and 16 g of cyclopentane were weighed at room temperature, shaken and mixed for 1 hour, and then mixed with 125 g of Wanhua PM-200. After stirring for 5 seconds, the mixture was quickly poured into a horizontal mold (size: 500 mm long, 500 mm wide, and 100 mm high). The mixture was quickly poured into an open horizontal mold, the lid was fastened, and the mold was demolded after 4 minutes. The foam was quickly taken out, and the average expansion value of the 6 points in the center was selected. The characterization results of the polyurethane foam are shown in Table 2.

[0086] Table 1 Analysis of indicators of regenerated polyether polyols in Examples and Comparative Examples

[0087]

[0088] Table 2: Example and comparative example, analysis of indicators of recycled polyurethane rigid foam prepared by foaming recycled polyether

[0089]

[0090]

[0091] It can be seen from the results of Example 1 and Comparative Example 1 that extraction can efficiently separate the reaction products, which is helpful to obtain high-functionality, low-viscosity regenerated polyether polyols.

[0092] From the results of Example 1 and Comparative Example 2, it can be seen that after the monofunctional small molecule alcohol undergoes an ester exchange reaction, the polarity of the obtained carbamate is small, which is greatly different from the polarity of the regenerated polyol, and is conducive to subsequent separation.

[0093] It can be seen from the results of Example 1 and Comparative Examples 3, 4, and 5 that within the weakly acidic system, the extraction efficiency of cyclohexane is relatively high, which is helpful for obtaining a regenerated polyether polyol with high functionality and low viscosity. It can be seen from the results of the Examples and Comparative Examples in Tables 1 and 2 that the regenerated polyether polyol obtained by the method of the present invention has a higher average functionality and a lower viscosity, and the polyurethane foam obtained by further foaming has a lower thermal conductivity and excellent demoulding performance, and has a higher compression strength under a lower core density condition, and a high closed cell rate, which meets the demand for polyurethane rigid foam in refrigerators, freezers, and other fields.

[0094] Those skilled in the art will appreciate that, based on the teachings of this specification, some modifications and adjustments may be made to the present invention, and these modifications and adjustments should also be within the scope defined by the claims of the present invention.

Claims

1. A method for efficiently preparing recycled polyether polyols using waste polyurethane materials, characterized in that: The following steps are involved: S1. Grind the waste rigid polyurethane foam material, add alcoholysis agent and catalyst in proportion, carry out alcoholysis reaction under an inert gas atmosphere, and centrifuge after the reaction is completed; S2. Take the upper liquid phase after centrifugation, add a neutralizing agent to adjust the pH, then transfer to a three-necked flask and continue heating for neutralization reaction. After the reaction is completed, centrifuge the alcoholysis product, cool it, add an extractant to extract and separate the liquid, and dehydrate the upper inorganic phase with a dehydrating agent to obtain a regenerated polyether polyol.

2. The method according to claim 1, characterized in that In S1, the waste rigid polyurethane foam material is crushed into particles with a diameter less than 30 mm, preferably less than 10 mm.

3. The method according to claim 1 or 2, characterized in that: The alcoholysis agent is selected from hydroxy alcohols with a single reaction site and low molecular weight, preferably one or two of methanol, ethanol, 1-propanol, 1-butanol, and 2-butanol, more preferably 2-butanol; Preferably, the mass ratio of the alcoholysis agent to the polyurethane material is 1:1 to 1:4, preferably 1:

2.

4. The method according to any one of claims 1 to 3, characterized in that: The catalyst is an organic metal compound, preferably any one of titanium butoxide, titanium ethylene glycol, potassium octoate, stannous octoate, and potassium acetate, more preferably potassium acetate; Preferably, the added amount of the catalyst is 0.3-1.5% of the total mass of the polyurethane material and the alcoholysis agent, preferably 0.8-1.2%.

5. The method according to claim 4, characterized in that The reaction temperature of the alcoholysis reaction in S1 is 130-170°C, and the reaction time is 3-6h.

6. The method according to any one of claims 1 to 5, characterized in that: The neutralizing agent is selected from any one of hydrochloric acid, oxalic acid, nitric acid, phosphoric acid, and dilute sulfuric acid, preferably hydrochloric acid; Preferably, the concentration of the neutralizer is 0.5 to 2 mol / L, preferably 1 mol / L, and the pH is adjusted to 5 to 7 by adding the neutralizer; More preferably, the reaction temperature of the neutralization reaction is 35 to 50° C., and the reaction time is 2 to 4 hours.

7. The method according to claim 6, characterized in that The extractant is selected from any one of ethyl acetate, carbon tetrachloride, gasoline, butanone, and cyclohexane, preferably cyclohexane; Preferably, the amount of the extractant added is 10-20% of the mass of the alcoholysis product.

8. The method according to claim 7, characterized in that The dehydrating agent is selected from any one of calcium chloride, anhydrous copper sulfate, magnesium chloride, and sodium carbonate, preferably calcium chloride; Preferably, the amount of the dehydrating agent added is 8-20% of the mass of the alcoholysis product.

9. The method according to any one of claims 1 to 8, characterized in that: The regenerated polyether polyol has an average functionality of 2 to 6, preferably 3 to 5, a hydroxyl value of 200 to 1000 mg KOH / g, preferably 300 to 400 mg KOH / g, a viscosity of 2000 to 12000 cp, preferably 3000 to 6000 cp, and an acid value of 0.1 to 1.5 mg KOH / g, preferably 0.2 to 0.5 mg KOH / g.

10. A polyurethane foam, characterized in that: The polyether polyol of the polyurethane foam comprises a recycled polyether polyol prepared by the method according to any one of claims 1 to 9, wherein the recycled polyether polyol accounts for 10% to 100% of the total mass of all polyether polyols, preferably 40 to 60%, and more preferably 50%; Preferably, the overall core density of the polyurethane foam is 26-33 kg / m 3 , compression strength Degree 140~180kPa, thermal conductivity 18~20.5mW / (m·k), water absorption 0.6~1%, The closed cell rate is 97-99%, and the average demoulding expansion is 1.7-3.8 mm.

Citation Information

Patent Citations

  • Degradable external emulsion waterborne polyurethane and preparation method thereof

    CN115677975A

  • Compositions containing polyether-polysiloxane block copolymers with improved foam enhancement, methods of use and manufacture thereof

    CN117580913A

Cited By

  • Method for preparing regenerated polyether polyol by degrading waste polyurethane semi-rigid foam through acidolysis method

    CN121554825A